Diffusion in the Iron Group L12 and B2 Intermetallic Compounds - Pelleg, Joshua (Engineering Materials, 2017)
This book explores diffusion in L12 and B2 structures of Ni3Al, Ni3Ge, Ni3Ga and NiAl, NiGe and NiGa and discusses Fe- and Co-based alloys in detail. These alloys of the VIIIA group elements are the basis of intermetallic compounds known as "super alloys," which are important in many technological high-temperature structural applications to improve mechanical strength properties such as creep. Knowledge of diffusion behavior of intermetallic solids is critical, in particular in high temperature applications of material. Development of high temperature alloys depends on the understanding of diffusion in the aforementioned compounds. Therefore, this comprehensive book on diffusion in the iron group (VIIIA) based intermetallic compounds will be of interest to students, lecturers and researchers. For engineers working in the aircraft industry, this book will prove invaluable as it contains fundamental up to date information and basic knowledge on materials of their interest.